Development of ductile iron alloy for ADI production using heated air in austempering - Leonardo Pereira; Willian Martins Pasini; Vinicius Karlinski de Barcellos (REM: International Engineering Journal)
Abstract Ductile iron is typically used in as-cast conditions. However, a typical heat treatment applied to ductile iron is austempering, which allows for increased tensile strength with good levels of elongation and toughness. The traditional means of austempering involves molten salt baths, but these baths have environmental and operational restrictions. Laboratory-level studies have found the feasibility of using heated air for cooling and holding during austempering. Due to the lower cooling severity of heated air, it is necessary to increase the austemperability of ductile iron. Elements that contribute to austemperability are manganese, copper, molybdenum, and nickel. This study used numerical, thermodynamics, and kinetics simulation to develop a suitable ductile iron alloy for obtaining ADI in a standard ASTM test specimen using heated air for cooling. According to the numerical simulation results, the average cooling rate between 900°C and 500°C in the critical region for air velocities of 5 m/s and 10 m/s at a temperature of 280°C ranged from 75°C/min to 82°C/min. Through thermodynamic and kinetic simulation, nickel has the most significant capacity to alter the austemperability of ductile iron. Based on these results, six ductile iron alloys with nickel contents ranging from 0.2 to 2% were developed. The experimental cooling rate is approximately 70°C/min, with the 3.41C, 2.72Si, 1.01Cu, 0.31Mn, 0.18Mo, and 1.13Ni alloy suitable for obtaining ADI.